2021
DOI: 10.3390/microorganisms9112339
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Indices of Plant Communities and Their Rhizosphere Microbiomes: An Attempt to Find the Connection

Abstract: The rhizosphere community represents an “ecological interface” between plant and soil, providing the plant with a number of advantages. Despite close connection and mutual influence in this system, the knowledge about the connection of plant and rhizosphere diversity is still controversial. One of the most valuable factors of this uncertainty is a rough estimation of plant diversity. NGS sequencing can make the estimations of the plant community more precise than classical geobotanical methods. We investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Other studies have noted mixed results on the association between host plant diversity and overall diversity of microbes in their rhizospheres. For example, Zverev et al ( 2021 ) did not find a correlation between alpha diversity of plants and rhizosphere bacteria in farmed and fallow fields, but Singh et al ( 2022 ) reported that alpha diversity varied among rice cultivars. These studies suggest a complex interplay of factors likely determine the level of microbial diversity associated with plants, as well as the specific types of microbes present.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have noted mixed results on the association between host plant diversity and overall diversity of microbes in their rhizospheres. For example, Zverev et al ( 2021 ) did not find a correlation between alpha diversity of plants and rhizosphere bacteria in farmed and fallow fields, but Singh et al ( 2022 ) reported that alpha diversity varied among rice cultivars. These studies suggest a complex interplay of factors likely determine the level of microbial diversity associated with plants, as well as the specific types of microbes present.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason could be plant-soil interaction. Different plant communities form specific rhizosphere communities [21] which leads to differences in soil microbial community. Differential taxonomic analysis in Q_R and pQ_R comparison reveals mostly common plant-associated bacterial genera, like previously described Aquispherae [22], Bradyrizobium [23] and Reyranella [24].…”
Section: Discussionmentioning
confidence: 99%
“…To study microbial diversity in the environment, the richness and diversity of the microbial community can be reflected by Alpha diversity analysis ( Rogers et al, 2016 ; Zverev et al, 2021 ) in a single sample. Alpha diversity refers to the diversity in a specific region or ecosystem.…”
Section: Methodsmentioning
confidence: 99%